Design and development of multistage symmetrical wobble compressor - Syahrom, Ardiyansyah (Faculty of Mechanical Engineering, 2006)
There are many types of compressor design based on variation applications from the low pressure to the high pressure compression. For the high pressure application, the horizontal opposed reciprocating compressor is the most popular. However, for the smaller flow-rate natural gas refueling appliance compressors, scotch-yoke type has just been introduced into the market. Judging from the advantages and disadvantages from these compressor types, the wobble-plate and swash-plate compressor were chosen to be the combined concept for development of the new compressor. Both compressor concepts are currently used only for low pressure application with single stage compression. For this new compressor design development, both compressor types were combined to develop into a new symmetrical multi-stage wobble-plate compressor. The new compressor design operates with the suction pressure of 3 bar and discharge pressure of 206 bar. This new compressor design inherits the advantages of the wobble-plate and the swashplate compressor which are compact and able to operate at high operating speed. Main improvement in this new compressor design is the introduction of the symmetrical wobble-plate configuration which allows for higher compressor capacity and balanced horizontal forces. The rotor concept from the swash-plate compressor has also been adopted in this new design. The normal connecting rod with the two ended ball joints has been replaced by the connecting rod with standard end-joints at both ends. This has eased the manufacturing process as the end-joints are available on the shelves. However, this standard universal end joint has limit the tilting angle of the wobble plate to a maximum of 16Âº. Against this limitation and for the compressor to operate with minimum possible operating torque and optimum pressure ratio, analysis conducted concludes that the optimum number of stages is five. Flow analysis was conducted to simulate pressure and gas velocity distributions. This has helped in the conceptual development and this design of the suction and discharge port, the value and the cylinder of each stage. Heat transfer analysis was also conducted to simulate the temperature distribution on the cylinder block. The predicted temperature is about 302ÂºC at the first stage. Temperature rise due to compression of the air for both prototypes was found to be insignificant. As such the inter-cooler and after-cooler provided were found unnecessary and were not used. Both prototypes operated with good stability at all speeds and noise generated was acceptably low. The 1.00 m3/hr prototype compressor was run at 1100 rpm producing a discharge pressure of 260 bar and for flow rates of 10 m3/hr was run at 400 rpm producing a discharge pressure of 180 bar.